Ketogenic diet improves fertility in patients with polycystic ovary syndrome: a brief report - Tsushima, Yumiko; Nachawi, Noura; Pantalone, Kevin M.; Griebeler, Marcio L.; Alwahab, Ula Abed (Frontiers in Nutrition, 2024)
Obesity plays a key role in the mechanism of infertility affecting up to 60% of women with PCOS.• Keto Diet (KD) improves characteristics of PCOS such as insulin levels, free testosterone, and LH/FSH ratio • The effect of Keto Diet on fertility in patients with PCOS is unknown.• The KD may improve ovulation and fertility rates in women with PCOS regardless of metformin or ovulation induction use. • Further prospective studies evaluating the impact of a KD on fertility appear warranted, as well as mechanistic studies to further elucidate the mechanism by which a KD may improve fertility, with or without weight loss.